Strategies for Performing Factor Assays in the Presence of Emicizumab or Other Novel/Emerging Hemostatic Agents - Kershaw, Geoffrey (Seminars in Thrombosis and Hemostasis, 2024)
For several decades, therapeutic options for inherited deficiencies of factor VIII or IX (hemophilia A or B, respectively) have largely been the replacement of the missing clotting factor with plasma-derived or recombinant products. Hemostasis laboratories use standard activated partial thromboplastin time (aPTT)-based clotting or chromogenic assays to monitor plasma factor levels to guide therapy. The emergence in the past 10 years of extended half-life replacement products and other novel therapies for hemophilia has led to a reappraisal of assay suitability, with studies of product measurement showing some existing assay types or reagents to be unsuitable for some products. The hemostasis laboratory must adapt to the changing landscape by adding new assays or modifying existing assays to ensure accurate results for product measurement. These strategies include switching from a chromogenic assay to a clotting assay, or vice versa, changing an aPTT reagent brand, or introducing product specific calibrators. This article evaluates the effects of some of the newer treatment options on the laboratory testing of factor levels and related assays.
Keywords: emicizumab; Mim8; rpFVIII; efanesoctocog alfa; FVIII